Application of the Chimney Cap as a Method of Improving the Effectiveness of Natural Ventilation in Buildings - Antczak-Jarząbska Romana; Niedostatkiewicz Maciej (Polish Maritime Research, 2020)
Adequately designed natural ventilation is the cheapest and easiest way to effectively remove indoor pollutants and keep the air inside a building fresh. A prediction of the performance and effectiveness of ventilation in order to determine the design of a ventilation system can provide real and long-term cost savings. The worst time in terms of the efficiency of natural ventilation is the spring-autumn transition period [7]. In order to improve the efficiency of natural ventilation, chimney caps are used, among others. They are designed to improve the chimney effect described in colloquial language as a chimney draft. The chimney effect is a physical phenomenon of the formation of a spontaneous flow of a warmer gas, e.g. air, from the bottom up in stem channels [12]. The article analyses the influence of the chimney cowl on the improvement of the chimney effect in an apartment of a multi-family building with natural ventilation. Long-term tests of the chimney draft were carried out for the case without and with a chimney cap. The paper presents the results of the performance (air change rate, ACH) of natural ventilation for a building with an inlet gap measured for the transitional season (between the heating and the summer season). The measurements were performed during a windy period.